Optimization, Development and evaluation of Microemulsion for the release of combination of Guaifenesin and Phenylephrine - S. N. Deepak and B. N. Vedha Hari (Journal of Applied Pharmaceutical Science, 2013)
Guaifenesin and Phenylephrine possess greater water solubility but lower permeability and bioavailability. The aim of this study is to develop a microemulsion to overcome these issues. Castor oil, Oleic acid and Emu oil were selected as oil phase. Tween 80 and Span 80 were selected as surfactants.2-propanol and ethanol were selected as co-surfactants. Optimization of co-surfactant was done by taking a series of O/W microemulsions which were formulated by titration method. 32 formulations were formed initially and based on various physical parameters like clarity, Stability, density, viscosity, pH and electrical conductivity, 17 formulations were narrowed down. The particle size study was carried out by zeta analysis and the results proved that the formulations were nano sized. FTIR studies proved that there was not much interaction between the drugs in the formulation. In-vitro dissolution studies were performed for all the 17 formulations individually for both the drugs was found. The optimum formulation where sustained release for both the drugs was found to be in the combination of Oleic acid: Tween 80: Water: 2-propanol (1:3:5:9). This formulation was subjected to ex-vivo diffusion study and the permeation through the membrane was found.
Keywords: Guaifenesin, Phenylephrine, Expectorant, Nasal Decon